2015
DOI: 10.1021/acs.jafc.5b02222
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Scope Screening of Illegal Adulterants in Dietary and Herbal Supplements via Rapid Polarity-Switching and Multistage Accurate Mass Confirmation Using an LC-IT/TOF Hybrid Instrument

Abstract: A new analytical strategy was developed that integrates a generic sample preparation into a liquid chromatography-multistage ion trap/time-of-flight mass spectrometry (LC-IT(MS(n))/TOF), allowing for large-scale screening and qualitative confirmation of wide-scope illegal adulterants in different food matrices. Samples were pretreated by a fast single-tube multifunction extraction for accurate multistage mass measurement on the hybrid LC-IT/TOF system. A qualitative validation performed for over 500 analyte-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…We utilized the automated combination of positive and negative ionization modes mass spectra derived from fast polarity switching that has been widely used in lipidomics and drug metabolomics area . This extension enables detection of metabolites in complex biological samples and provided complementary identification of untargeted metabolomics . Owing to fast polarity switching approach, two total ion chromatograms as well as averaged mass spectrum clearly revealed its benefit of complementary recognition gained from the integration of two ionization modes as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We utilized the automated combination of positive and negative ionization modes mass spectra derived from fast polarity switching that has been widely used in lipidomics and drug metabolomics area . This extension enables detection of metabolites in complex biological samples and provided complementary identification of untargeted metabolomics . Owing to fast polarity switching approach, two total ion chromatograms as well as averaged mass spectrum clearly revealed its benefit of complementary recognition gained from the integration of two ionization modes as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of these anthocyanidins and the 11 observed anthocyanins in the C. caudatus extracts are illustrated in Table 4, along with their molecular weights. The high-resolution time-of-flight (TOF) mass spectrometer (HRMS) with mass-resolving power of ≥10,000 at the full width at half maximum (FWHM) of a peak, sub-ppm (parts per million) mass measurement error, and characteristic sensitive full-spectrum scanning allowed the calculation of accurate elemental formulae and the elucidation of the anthocyanin identities in the C. caudatus extracts [58][59][60]. The generated molecular formulae were then compared to previous reports on anthocyanins, as listed in Table 5.…”
Section: Metabolomic Analysismentioning
confidence: 99%
“…Common adulterants include erectile dysfunction, anti‐hypertensive, anti‐diabetic, and anti‐obesity drugs 10–13 . In addition, in recent years, lovastatin, lovastatin acid and bezafibrate have been found unexpectedly in red yeast rice supplements 14–16 . This adulteration presents a serious threat to consumer health because of a lack of data or inaccurate safety data, as well as the potential for undesirable side effects 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Fukiqake et al reported an ultra‐performance liquid chromatography (UPLC) method using an ultraviolet (UV) detector for the simultaneous determination of 12 statins in dietary supplements 14 . Guo et al reported an LC/ion trap time‐of‐flight mass spectrometry method for the screening of various drug compounds including five statins and two fibrates in dietary supplements 15 . In addition, Cohen et al reported a method for the determination of lovastatin in dietary supplements using an UPLC system equipped with a diode‐array detector and a quadrupole time‐of‐flight mass spectrometer 16 Recently, Di Donna et al analyzed lovastatin‐containing dietary supplements using LC/tandem mass spectrometry (LC/MS/MS) 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation